‘High Standard of Efficiency and Steadiness’: Papua New Guinea Native Police Guards and Japanese War Criminals, 1945–53 - Boyd, James; Morris, Narrelle (Routledge, 2015)
Drawing largely on archival records, this paper examines the Australian use of a detachment from the Native police force to guard the Australian war criminals’ compounds for Japanese war criminals established at Rabaul and Manus Island, both in the Territory of New Guinea, from 1945 to 1953. Australia was the only Allied country in the immediate post-war period to utilise civilian police as guards for Japanese war criminals, let alone to draw principally upon Indigenous personnel. While Australian views of the Indigenous population remained paternalistic, if not outright racist, throughout this period, the use of the Native police opened up some small spacefor more complex perceptions of questions of racial difference. Yet, the Native policedetachment to the Australian war criminal compounds has been, until now, generally overlooked in the broader history of the Native police forces of Papua and of New Guinea.